Evaluation of the Tempo® System: Improving the Microbiological Quality Monitoring of Human Milk - Cayer, Marie-Pierre; Dussault, Nathalie; de Grandmont, Marie Joëlle; Cloutier, Marc; Lewin, Antoine; Brouard, Danny (Frontiers in Pediatrics, 2020)
Background: Bacteriological testing of donor human milk is mostly done both before and after pasteurization to control contamination in the end-product and meet the microbiological standards. Although the plate count method represents a reliable and sensitive technique and is considered the gold standard for bacteriological testing, it is recognized for being time-consuming and requiring qualified personnel. Recently, faster testing technologies, mostly geared towards the food industry, have been developed. Among these, the bioMérieux TEMPO® system uses the most probable number method to assess microbiological content in a semi-automated fashion. Objective: The performances of the TEMPO® system in enumerating bacterial quality indicators in human milk were assessed and compared to the reference plate count method. Methods: Naturally and artificially contaminated human milk samples were used to compare the analytical performances of the TEMPO® system to the plate count technique. More specifically, bacteria belonging to the genera Bacillus, Enterobacteriaceae, Staphylococcus aureus and total aerobic flora were screened using both methods. Bacteria isolated on agar plates containing selective media were identified by supplemental testing. Bacterial testing results and method parameters were compared using linear regression analyses and Bland-Altman approaches. Results: Naturally contaminated milk samples (n = 55) tested for total aerobic flora showed < 1 log (CFU/mL) discrepancy between the two methods in the output results for 98% of the samples. Comparative linear regression analyses demonstrate good correlations between the two methods (R2 > 0.9). At lower levels of bacterial contamination, the TEMPO® method precision (C.V. < 8%) and accuracy (> 83%) were comparable to plate counts. Conclusions: The analytical performances of the TEMPO® system for human milk bacteriological testing are equivalent to the reference plate count method. Results from the TEMPO® system are available within a 24-hour turnaround time from sample inoculation without the need for further supplemental testing, suggesting that this semi-automated method could be implemented within milk bank operations as an in-process monitoring technology to optimize end-product quality and safety.